O34-2 Insomnia and the older worker: findings from the health and employment after fifty (HEAF) study. (1st September 2016) - D'Angelo, Stefania; Harris, EC; Linaker, Catherine; Sayer, Avan Aihie; Gale, Catharine; Evandrou, Maria; Staa, Tjeerd Van; Cooper, Cyrus; Coggon, David; Walker-Bone, Karen; Palmer, Keith T
Abstract : Background: Sleep disturbance is highly prevalent among people of working age, and has been linked with negative occupational outcomes including impaired productivity, absenteeism, risk of injuries, and health-related job loss. We aimed to describe the epidemiology of insomnia in HEAF, a cohort study of 50–64 year-olds from 24 English general practices, and to explore the relative importance of different occupational risk factors for insomnia. Methods: Data came from the baseline questionnaire of the HEAF study. Participants reported on four problems with their sleep in the past 3 months, and insomnia was defined as having at least one severe problem. Socio-demographic variables, employment conditions and feelings about work were also ascertained. Analysis was restricted to those who answered the question on sleep disturbance (N = 8, 067) and for the occupational analyses, to those in work (N = 5, 470). Associations were assessed by logistic regression with adjustment for age and sex, and population attributable fractions (PAFs) were also computed. Results: Insomnia was reported by 18.8% of the participants. It was more common among women, current smokers, manual social classes, and in those with lower educational level, living alone, experiencing financial hardship and who were obese. It was less prevalent among older people and those socialising with friends. Unemployed people tended to report more insomnia (OR = 3.1, 95% CI: 2.6–3.8), as did those in shift work (OR = 1.4, 95% CI: 1.2–1.7), dissatisfied with their job (OR = 3.9, 95% CI: 3.1–4.9), and rarely feeling appreciated (OR = 2.5, 95% CI: 2.1–3.1), or feeling unfairly criticised at work (OR = 4.2, 95% CI: 3.0–6.1). Population burden of insomnia was associated particularly with difficulties in coping with work demands, job insecurity and difficult colleagues (PAFs 17–33%). Conclusions: Our data suggest that insomnia may be linked to several workplace elements that are potentially avoidable through better employment practices and policies.